DIMENSIUNI CONCEPTUALE ALE CUNOAŞTERII ŞTIINŢIFICE ÎN PROCESUL EDUCAŢIONAL - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2007)
In the article there was analysed the concept of scientific inquiry, the fundamental levels of scientific inquiry: empi- rical – receptive and theoretical – rational, the stages of shaping of scientific inquiry, the conceptual nucleus of scientific theory and its functions.